Khul' Menurut Imam Syafi'i dan Imam Hanbali: Mencari Relevansinya di Indonesia - Edi Kurniawan; Ulul Albab Fadhlan; Illy Yanti (AL-HUKAMA, 2020)
Khul' or divorce requested by a wife is one of the causes marital termination. According to Imam Syafi'i, khul' is a divorce (talak) with an 'iddah of three menstruat cycles. In contrast, for Imam Hanbali, khul' is fasakh in which its 'iddah is one menstrual cycle and its legality does not require a judge's decision. This difference has dissimilar legal implications when it is applied in Indonesia. Therefore, this article aims to seek the both relevancies in the context of Indonesian law, especially under the Compilation of Islamic Law and the nature of the religious practice of Indonesian Muslims. After examining the relevant literature sources, this article shows that, both Imam Syafi'i and Imam Hanbali agree that khul' is like a buy-sell contract, and hence a judge's decision is not required. However these both agremeents are not relevance under the Compilation of Islamic Laws, but the Imam Hanbali's fiqh in which khul' as fasakh would be difficult to seek its relevance. Thus, the fiqh of Imam Syafi'i is more appropriate, since beside it is used as a basis for the Compilation of Islamic Laws the majority of Indonesian Muslims embrace the Syafi’i mazhab.